Virulence attenuating combination therapy: a potential multi-target synergy approach to treat Pseudomonas aeruginosa infections in cystic fibrosis patients. Issue 3 (19th February 2020) - Shaw, Elana; Wuest, William M.
Abstract : Virulence attenuating combination therapy may be a promising approach to treating chronic P. aeruginosa infections in patients with cystic fibrosis. Abstract : The World Health Organization considers the discovery of new treatments for P. aeruginosa a top priority. Virulence attenuating combination therapy (VACT) is a pragmatic strategy to improve bacterial clearance, repurpose outmoded antibiotics, improve drug efficacy at lower doses, and reduce the evolution of resistance. In vitro and in vivo studies have shown that adding a quorum sensing inhibitor or an extracellular polymeric substance repressor to classical antibiotics synergistically improves antipseudomonal activity. This review highlights why VACT could specifically benefit cystic fibrosis patients harboring chronic P. aeruginosa infections, outlines the current landscape of synergistic combinations between virulence-targeting small-molecules and anti-pseudomonal drugs, and suggests future directions for VACT research.